Washback Effects of the New CET4 Listening Test on College English Listening Teaching and Learning - Wang, Chao (Advances in Social Sciences Research Journal, 2023)
As a high-stake and criterion-related norm-referenced test which is intended to supervise the implementation of Syllabus and diagnose the strength and weakness in college English teaching and learning, CET4 (College English Test Band-4) exerts both beneficial and harmful effects on English education. Conducted respectively from the perspectives of teaching and learning attitude, materials and strategies, the study is mainly aimed to explore the possible washback effects of the new CET4 listening subtest on college English teaching and learning. A combination of both qualitative and quantitative approaches was adopted to research on 10 English teachers and 50 students from Beijing Institute of Petrochemical Technology. The findings reveal that the new CET-LT has made satisfactory innovations in test format and input materials, and it has more beneficial washback effects on college English teaching and learning. However, the phenomenon of “teaching and learning to test” still exists in our educational practice, which affects the efficiency of EFL teaching and learning in China.